Catalytic study of modified titanium silicalites-1 in the hydroxylation of alkyl benzene by hydrogen peroxide - Pornapa Kasemsiri (Chulalongkorn University, 2014)
Thesis (M.Eng.)--Chulalongkorn University, 2007